The Use of Avian Yolk Antibodies in the Inactivation of Highly Toxic Components of Biological Weapons and Especially Dangerous Infections - V. S. Kaplin (Вестник войск РХБ защиты, 2023)
Currently, Western pharmaceutical companies have mastered the production of licensed drugs based on transovarial chicken specific antibodies (IgY antibodies) intended for the treatment and prevention of infections caused by Helicobacter pylori, influenza virus and other pathogens. Of particular interest is the possibility of using IgY antibodies as an inexpensive specific antidote for emergency specific prevention of infections caused by pathogens of dangerous and especially dangerous infections. The purpose of this work is to summarize the results of studies that have shown a high therapeutic potential of transovarial specific immunoglobulins in the treatment and prevention of dangerous viral, bacterial infections and injuries by biological toxins – potential agents of biological weapons (BW). The advantage of using IgY technologies for passive immunization is a non-invasive method for obtaining antibodies, as well as a large amount of them – 20–30 g of immunoglobulins, which can be obtained from one laying hen per year. An important advantage of IgY over immunoglobulins derived from mammalian serum is that they do not interact with complement components, nor with rheumatoid factor, nor with Fc receptors of mammalian immunocompetent cells, which significantly reduces the manifestation of adverse reactions, in particular, antibody-dependent enhancement of infection (ADE). Experiments carried out in vivo and in vitro showed a high activity of IgY antibodies in suppressing the damaging effect of pathogens of especially dangerous infections and biological toxins. It is shown in the article, that the replacement of mammalian IgG with avian transovarial IgY allows obtaining commercially significant amounts of thermostable specific antibodies that do not cause ADE, and expands the possibilities of methods for specific prevention and treatment of lesions caused by viruses, bacteria, and toxins – potential agents of biological weapons.